Molecular Characterisation and Antimicrobial Resistance Patterns of Shiga Toxin Producing Escherichia coli Isolated from Farm Water Samples - Putturu, Ramya; Kumar, Manyam S.; Babu, Angalakudithi J.; Singh, Sujatha; Reddy, Alla G. (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
Shiga toxin-producing Escherichia coli (STEC) strains are considered the most common food-borne zoonotic pathogen and are highly  pathogenic to humans in low infectious doses, causing food-borne diseases through consumption of contaminated water or food.  Resistance against antibiotics by STEC is a big concern nowadays. Two hundred farm water samples (Cattle-40, Buffaloes-40, Sheep-30,  Goat-20, Pig-20 and poultry-50) were collected aseptically from different livestock farms in and around Proddatur, Andhra Pradesh, India  and Processed for E. coli isolation, identification with culture method and molecular characterization by PCR. E. coli was characterized  as STEC with two genes i.e. stx1 and stx2. All the STEC isolates were subjected to an antibiotic sensitivity test by disc diffusion method  against ten antibiotics. Results showed that out of 200 farm water samples, 196 were positive for E. coli with an overall prevalence of 98%  (196/200) and 62.2% (122/196) for STEC by PCR. Antimicrobial susceptibility test by disc diffusion method against ten antibiotics revealed  the higher resistance to Cepahlothin (100%) followed by Tetracyclin (98.4%), Ampicillin (96.7%), Streptomycin (95%), Sulphonamides  (91.8%), Trimethoprim (84.4%), Kanamycin (34.4%), Chloromphenicol (17.2%), Colistin (9.0%) and least resistance to Gentamycin (4.9%).
Keywords: Antimicrobial resistance; Escherichia coli; Farm water samples; Shiga toxin producing